2009
DOI: 10.1007/s00035-009-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

Gradual decline in genetic diversity in Swiss stone pine populations (Pinus cembra) across Switzerland suggests postglacial re-colonization into the Alps from a common eastern glacial refugium

Abstract: Molecular genetic markers may reveal informative patterns of population processes such as historical migration, which may substantiate inference on postglacial re-colonization inferred, e.g., from fossil records. Palynological records of Swiss stone pine (Pinus cembra) suggest that the species has re-colonized the central Alps from a southeastern Alpine refugium after the last glacial maximum. Such a migration pathway likely resulted in a gradual decrease in genetic diversity with increasing distance to the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 42 publications
7
36
0
1
Order By: Relevance
“…3). Overall, the pattern of genetic differentiation of Swiss stone pine is rather shallow (Belokon et al 2005;Gugerli et al 2001Gugerli et al , 2009Höhn et al 2009), indicating recent fragmentation of a common gene pool that formerly occupied a larger range. …”
Section: Patterns Of Genetic Diversitymentioning
confidence: 97%
See 1 more Smart Citation
“…3). Overall, the pattern of genetic differentiation of Swiss stone pine is rather shallow (Belokon et al 2005;Gugerli et al 2001Gugerli et al , 2009Höhn et al 2009), indicating recent fragmentation of a common gene pool that formerly occupied a larger range. …”
Section: Patterns Of Genetic Diversitymentioning
confidence: 97%
“…Such structure may be a result of spatial isolation hampering gene flow among fragmented populations. In the Alps, Gugerli et al (2009) found a gradual decline of chloroplast DNA diversity from East to West, along the colonization route from a single glacial refugium located at the (south-) eastern periphery of the Alps. This pattern is in accordance with the ''abundant center model'' and reflects the process of genetic drift through founder events and/or bottlenecks, coupled with reduced gene flow related to postglacial colonization dynamics.…”
Section: Patterns Of Genetic Diversitymentioning
confidence: 99%
“…In conifers, nSSRs are applied in multiple research areas such as population studies (e.g., Marshall et al 2002;A 0 Hara and Cottrell 2004;Waldmann et al 2005;García-Gil et al 2009;Gugerli et al 2009;Tollefsrud et al 2009), genetic map construction (Pelgas et al 2006;Echt et al 2011) and paternity analysis (Lian et al 2001;Torimaru et al 2009). Despite the wide application of nSSRs, examples on the application of SSR multiplexing in conifers remain scarce (Devey et al 2002;Bell et al 2004;Karhu et al 2006;Gugerli et al 2009;Salzer et al 2009;Kawase et al 2010;Wagner et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…postglacial range formations are mainly affected by the recolonization routes. it is also largely accepted that founder events towards the edge of a species' range cause the gradual decrease of the population genetic diversity [17,6]. finally, the genetic parameters of the existing populations are determined by biogeographical characteristics, gene flow and effective populations size [3,13].…”
mentioning
confidence: 99%